Estimates of global research productivity in using nicotine replacement therapy for tobacco cessation: a bibliometric study - Sa'ed H. Zyoud (BMC, 2018)
Abstract Background Tobacco use is a major healthcare problem worldwide. Tobacco smoking remains the most important risk factor for both cancer and heart diseases. This study was initiated due to the lack of published data concerning the real progress in research output in the use of nicotine replacement therapy (NRT) for tobacco cessation. This study was aimed to use bibliometric analysis to estimate the NRT literature indexed in Scopus database at global level. Methods Core of the search strategy was the documents that contained specific words or phrases regarding NRT as keywords in the title. Publication output of most prolific countries was adjusted to the gross domestic product and population size. All citations analysis were accomplished on December 22, 2017. Results A total of 2138 references were retrieved and published from 56 countries, which were published between 1970 and 2016. The USA has the most number of published articles accounted to 986, followed by the UK (312 publications) and then Australia (102 publications), and Sweden (102 publications). No data related to NRT were published from 156 countries. No significant correlation was found between the country population size or 2016 gross domestic product values and the number of publications of the top-10 most prolific countries in the field of NRT (r = − 0.156, P = 0.664; and r = − 0.173, P = 0.632, respectively). Furthermore, there is no correlation between prevalence of tobacco smoking and number of publications of the top-10 most prolific countries in the field of NRT (r = − 0.235, P = 0.514). Conclusions The present data reveal a solid mass of research activity on NRT. The USA was by far the predominant country in the amount of NRT-based research activity. NRT-based research activities were low or not available in most countries. The results of this study delineate a framework for better understanding the situations of current NRT research and prospective directions of the research in this field which could be applied for managing and prioritizing future research efforts in NRT research.